Conceptual basis of economic and business culture of PRC - Бaйсұлтaновa, К. Ш.; Мaулит, Б. (Journal of Oriental Studies, 2018)
This article covers the concept of business culture and analyzes the peculiarities of China’s economic and business culture. The authors have analyzed the relationship between Chinese traditional culture and modern Chinese economic and business culture. The influence of Chinese CNPC traditional cultureon the Chinese business culture has been studied.